2012
DOI: 10.1016/j.psychres.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of serotonergic antidepressant usage in prodromal Huntington disease

Abstract: Antidepressant usage in prodromal Huntington Disease (HD) remains uncharacterized, despite its relevance in designing experiments, studying outcomes of HD, and evaluating the efficacy of therapeutic interventions. We searched baseline medication logs of 787 prodromal HD and 215 healthy comparison (HC) participants for antidepressant use. Descriptive and mixed-effects logistic regression modeling characterized usage across participants. At baseline, approximately one in five prodromal HD participants took antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…However, female participants had a higher current use of anxiolytics only, and not antidepressants. Findings from the PREDICT-HD study, involving predominantly prodromal HD carriers, revealed a sex difference in antidepressant use, with females being more commonly prescribed this medication [49]. Therefore, findings from the current study, involving a majority of those who were motor manifest, may reflect that as the disease progresses more men are subsequently prescribed antidepressant medication.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, female participants had a higher current use of anxiolytics only, and not antidepressants. Findings from the PREDICT-HD study, involving predominantly prodromal HD carriers, revealed a sex difference in antidepressant use, with females being more commonly prescribed this medication [49]. Therefore, findings from the current study, involving a majority of those who were motor manifest, may reflect that as the disease progresses more men are subsequently prescribed antidepressant medication.…”
Section: Discussionmentioning
confidence: 63%
“…A further explanation for the varying findings between humans and animals perhaps may highlight that the measurement and aetiology of depression is not equivocal, with the need to further consider psychological and social contributions to depression among humans (disparities for women, perceptions of stress, coping styles, cognitive appraisals, reduced employment opportunities and lower social status) [16,17]. For example, the reduction of any gender differences in depression may have been due to women seeking help for depression, as was found among our sample, women were found to have been more likely to have used both anxiolytics and antidepressants in the past, therefore indicative that they may have been more likely to previously seek help for their condition [49].…”
Section: Discussionmentioning
confidence: 81%
“…Of those, the majority took serotonergic antidepressants (selective serotonin reuptake inhibitors [SSRIs] or serotonin-norepinepherine reuptake inhibitors [SNRIs]), which was significantly higher than a healthy comparison group. Moreover, findings suggest that antidepressant usage increased as proximity to estimated motor manifestations increased [38]. A case series using the SNRI antidepressant venlafaxine XR for 4 weeks in a sample of 26 individuals with HD and depression reported a significant reduction in depressive symptoms [39].…”
Section: Treatment Of Depression In Hdmentioning
confidence: 99%
“…Investigating antidepressant usage in prodromal HD patients, Rowe and colleagues found that more female HD patients were prescribed antidepressants than males (Rowe et al, 2012), an indicator of higher rates of depression. This finding is further endorsed by another study which found that female HD patients had significantly higher rates of past and current depression than male patients (Zielonka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%